Two novel strains of Bacillus thuringiensis toxic to coleopterans. - Rupar, M J (1991)
Two novel strains of Bacillus thuringiensis were isolated from native habitats by the use of genes coding for proteins toxic to coleopterans (cryIII genes) as hybridization probes. Strain EG2838 (isolated by the use of the cryIIIA probe) contained a cryIIIA-hybridizing plasmid of approximately 100 MDa and synthesized crystal proteins of approximately 200 (doublet), 74, 70, 32, and 28 kDa. Strain EG4961 (isolated by the use of a cryIIIA-related probe) contained a cryIIIA-hybridizing plasmid of approximately 95 MDa and synthesized crystal proteins of 74, 70, and 30 kDa. Structural relationships among the crystal proteins of strains EG2838 and EG4961 were detected; antibodies to the CryIIIA protein toxic to coleopterans reacted with the 74- and 70-kDa proteins of EG2838 and EG4961, antibodies to the 32-kDa plus 28-kDa proteins of EG2838 reacted with the 30-kDa protein of EG4961, and antibodies to the 200-kDa proteins of EG2838 reacted with the 28-kDa protein of EG2838. Experiments with B. thuringiensis flagella antibody reagents demonstrated that EG2838 belongs to H serotype 9 (reference strain B. thuringiensis subsp. tolworthi) and that EG4961 belongs to H serotype 18 (reference strain B. thuringiensis subsp. kumamotoensis). A mixture of spores plus crystal proteins of either EG2838 or EG4961 was toxic to the larvae of Colorado potato beetle (Leptinotarsa decemlineata), and significantly, the EG4961 mixture was also toxic to the larvae of southern corn rootworm (Diabrotica undecimpunctata howardi). DNA restriction blot analysis suggested that strains EG2838 and EG4961 each contained a unique gene coding for a protein toxic to coleopterans.